Brand logo and brand personality perceptions: A case of real estate business in Thailand - Mittheera Leelayudthyothin; Amon Boontore (My University, 2022)
Brand logo is one of the key elements of corporate identity that most organizations use in differentiating its brand from others.A well-designed logo can be powerful in a competitive market, especially for the business whose identity and personality are highly required such as real estate.The annual revenue of Thai property business was reviewed and two groups of property brands were adopted as our case study including top ten and general selling brands.The objectives of this research were to examine the effects of logo elements including brand name, graphic, and color on brand logo perceptions in terms of uniqueness, recognition, and beauty and to explore brand personality perceptions comprising sophistication/up-to-date, excitement/friendliness, security/trustworthiness, and simplicity/sincerity of the representatives of both groups.A total of 486 participants served as our samples in evaluating brand logo elements and brand personality through questionnaire interviews.T-test and Chi-Square statistics were utilized in data analysis.The findings indicated that the whole logo should be advised in logo design guidelines for property brand rather than adopting individual element of logo separately to obtain positive perceptions in uniqueness, recognition, and beauty.Additionally, the study suggested that the specific brand personality had no connection with its stakeholders.
Keywords: Logo (programming language); Brand extension; Consumer Behavior in Brand Consumption and Identification